The Capability of Rice Plant Waste Sourced from the Feed Concentration Index in Farmer Groups in Salo Urban Vilagge - Surya Surya; Rahmaniar Rahman; Fitriawaty Fitriawaty; Ida Andriani; Azhar Amir (Faculty of Animal Science, Universitas Gadjah Mada, 2023)
This study aims to determine the characteristics of farmer groups, rice plant waste production, livestock performance, livestock economic density and feed concentration index in Salo Urban Village. This study uses a descriptive cross-sectional research design. Data were analyzed to look at the characteristics of farmer groups according to sex and age, rice plant waste production, livestock performance, livestock economic density and feed concentration index in Salo Urban Village. The results showed 23 farmer groups with 1.077 members, 937 male (87%) and 140 female (13%). There were 2 categories: the productive category for those aged 15 - 64 years old (85,24%) and the unproductive category for those over 65 years old (14,76%). The average harvested area is 39,18 Ha/farmer group; with fresh production of rice plant waste being 465,80 tons; dry production of rice plant waste being 263,65 tons; and dry matter production being 233,49 tons. The livestock performance equation is In (Y) = -348.47 + 0.18t with a growth rate of 18% for cattle and In (Y) = -340.38 + 0.17t with a growth rate of 17% for goats, and has an economic density of livestock in the rarely category. The feed concentration index obtained three categories, namely the high production category (1 farmer group), the medium production category (6 farmer groups) and the low production category (16 farmer groups). Shows that rice plant waste harvested from farmer groups in Salo Urban Village can be used as a ruminant feed source.